BUDAYA MENULIS: SEBUAH EKSISTENSI GURU GEOGRAFI DALAM PENGEMBANGAN KEPROFESIAN BERKELANJUTAN - Singgih Prihadi; Djoko Subandriyo; Sugiyanto Sugiyanto; Sarwono Sarwono (SEMAR (Jurnal Ilmu Pengetahuan, Teknologi, dan Seni bagi Masyarakat), 2017)
This research aims to 1) Improve the ability to write scientific papers for teachers of Geography in Boyolali district and Sragen; 2) Improving the understanding of teachers in the publishing of scientific papers in journals and popular science magazines. This research uses the questionnaire method described in deskripstif qualitatively. The teachers gathered in a workshop related scientific papers followed by filling the questionnaire. This method is deliberately done to facilitate the coordination of collecting data from informants. Data retrieval is packaged in the form of activities that preceded the workshop is considered effective to gather teachers, which in this study as an informant. To deepen the data generated from the questionnaire, research activities continued in the form of coaching and mentoring teachers to write scientific papers by submitting scientific papers to the editors of scientific journals.Results of research in the form of training and mentoring the writing of scientific papers proven to optimize the climate and teacher motivation in writing scientific articles and research results in the form of ideas. Articles are arranged expected to be published in national scientific journals ISSN. Besides the training and mentoring is very helpful teachers to obtain credit in the number of scientific publications. Writing scientific articles become an important and integral part in efforts to improve teacher quality through continuous professional development. Teachers spearhead educational success, but on the other hand teachers must constantly develop oneself to work. Budget allowance teacher certification it should be used for the development of self toward the professionalism of teachers.Keywords : scientific article, mentoring, teacher of geography